Physical and Chemical Characterization of Oil Extracted from Citrofortunella Microcarpa, Hibiscus Sabdariffa and Artocarpus Heterophyllus Seeds - Fai, Soon Zheng; Cheok, Choon Yoong (Progress in Energy and Environment, 2022)
Consumable plant oils had been related with highly nutritional content and antioxidant source that provide crucial health benefits. Hence, in this study a series of experimental work and analysis were conducted to evaluate the practicability and the properties of oil extraction from seeds of calamansi (Citrofortunella microcarpa), roselle (Hibiscus sabdariffa), and jackfruit (Artocarpus heterophyllus). The yield, antioxidant activities, iodine value, saponification value, and peroxide value of extracted seed oils were studied. Results obtained shown that among the three seeds species, calamansi seeds resulted in the highest yield of 32.7%, followed by roselle seeds with a yield of 11.00% and lastly, jackfruit seeds with the highest yield obtained was only 0.60%. Antioxidant activities conducted has shown that roselle with EC50 of 49.04 mg/mL has greater antioxidant properties as compared with calamansi with EC50 of 109.74 mg/mL. Iodine value determined for unheated oil has resulted in a value of 100.83 g I2/100g oil and 110.60 g I2/100g oil that has classified roselle and calamansi seeds oil under the non-drying oil categories and heating effect shown a slight decrease in the iodine value due to loss of unsaturation within the oil. Both calamansi and roselle seed oils did not show significance reduction in saponification value upon heating. Peroxide value for roselle and calamansi seeds oil under unheated condition was determined to be 10.36 meq/kg and 24.86 meq/kg respectively.